Public Private Institutional Partnerships (PPIPs) in South Africa : the case of service delivery in the health and social development sectors in the Sedibeng District Municipality - Kuye, Jerry O. (University of Pretoria, 2015)
Dissertation (PhD)--University of Pretoria, 2015.